2016
DOI: 10.3390/ijerph13090869
|View full text |Cite
|
Sign up to set email alerts
|

Phytoestrogens and Mycoestrogens Induce Signature Structure Dynamics Changes on Estrogen Receptor α

Abstract: Endocrine disrupters include a broad spectrum of chemicals such as industrial chemicals, natural estrogens and androgens, synthetic estrogens and androgens. Phytoestrogens are widely present in diet and food supplements; mycoestrogens are frequently found in grains. As human beings and animals are commonly exposed to phytoestrogens and mycoestrogens in diet and environment, it is important to understand the potential beneficial or hazardous effects of estrogenic compounds. Many bioassays have been established … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…On the other hand, ERβ is considered to have an antiproliferative effect and shows overexpression in normal tissues [ 16 , 17 , 18 ]. It is important to mention that both BPA and ZEA are able to interact with ERα according to previous studies [ 9 , 19 ]. Estrogen action is also mediated through ER-independent pathways (e.g., by G-protein coupled ERs) and the significance of epigenetic regulatory mechanisms has also been confirmed recently [ 15 ].…”
Section: Introductionmentioning
confidence: 88%
“…On the other hand, ERβ is considered to have an antiproliferative effect and shows overexpression in normal tissues [ 16 , 17 , 18 ]. It is important to mention that both BPA and ZEA are able to interact with ERα according to previous studies [ 9 , 19 ]. Estrogen action is also mediated through ER-independent pathways (e.g., by G-protein coupled ERs) and the significance of epigenetic regulatory mechanisms has also been confirmed recently [ 15 ].…”
Section: Introductionmentioning
confidence: 88%
“…It was known that phytoestrogens simulates estrogen effects, also, it was reported that they have beneficial effects on the bone health and bone regeneration (Lagari et al, 2013). Fisetin is a kind of phytoestrogen (Chen et al, 2016). BMSCs are multipotent stromal cells that can differentiate into mesenchymal cell lineages, such as; osteogenic, adipogenic, myogenic and chondrogenic lineages, many studies have been done on the use of mesenchymal stem cells for bone formation (Guihard et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Fisetin (3,3′,4′,7‐tetrahydroxyflavone) is a flavonoid phytoestrogen found in fruits and vegetables at 2–160 μg/g (Lall et al, 2016). Fisetin has been shown to have anti‐cancer, anti‐coagulatory, and anti‐inflammatory properties (Chen et al, 2016; Long et al, 2020). It also protects against oxidative stress‐related disorders such as diabetes and cardiovascular disease (CVD) (Li et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Fisetin has been shown to have anti-cancer, anti-coagulatory, and anti-inflammatory properties (Chen et al, 2016;Long et al, 2020). It also protects against oxidative stress-related disorders such as diabetes and cardiovascular disease (CVD) (Li et al, 2022).…”
mentioning
confidence: 99%